ANALISIS RISIKO OPERASIONAL AKIBAT KERUSAKAN PACKAGING DAN FERRO NICKEL PADA PERUSAHAAN LOGISTIK SURABAYA MENGGUNAKAN METODE FMEA DAN FISHBONE DIAGRAM - Nurin Cahyantika; Gaguk Suhardjito; Yugowati Praharsi (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
The Surabaya Logistics Company has a form of integration of all Freight Forwarding businesses in general, starting from the goods sent to the goods arriving at the destination country. In all Freight Forwarding business activities, problems are certainly not spared. The problems that occur are packaging damage and Ferro Nickel. Damage to the packaging and Ferro Nickel occurred because the Hoang Trieu 69 or break bulk ship did not use a professional guide ship so the Hoang Trieu 69 or break bulk ship hit a coral reef which couldtear the ship's wall. Damaged packaging and Ferro Nickel resulted in less effective operational activities. This loss has an impact on operational activities at the Surabaya Logistics Company. The purpose of this research is to identify and analyze the problem, theconsequences it causes, and the solution to the problem. So this study uses the Failure Modeand Effect Analysis (FMEA) method to look for risks that are processed to calculate the RiskPriority Number (RPN) and critical risks found in the Surabaya Logistics Company. Criticalrisks are used to find the root cause using the Fishbone Diagram method. In this study uses the Failure Mode and Effect Analysis (FMEA) method and the Fishbone Diagram method. The results of the study show that there is 1 critical risk that requires risk management. In handling risk at the Surabaya Logistics Company, it uses 4 strategies, namely immediate action, immediate attention, periodic attention, and annual evaluation. So this research was conducted to minimize the future of the Surabaya Logistics Company.